Diabetes and two kinds of primary tumors in a patient with thalassemia: a case report and literature review - Yu, Xiaoyan; Peng, Yi; Nie, Tingting; Sun, Wenjia; Zhou, Yajuan (Frontiers in Oncology, 2023)
Background Thalassemia is a group of common genetic hematologic disorders characterized by deficient synthesis of the hemoglobin chain. Due to effective blood transfusion and optimization of chelate therapy, the survival of thalassemia patients and their overall quality of life have improved noticeably in the past few decades. As a consequence, the longer life expectancy has led to the manifestation of several concomitant morbidities, including heart disease, infections, cirrhosis, endocrine abnormalities, various malignancies, and so on. In this context, the probability and updated literature about some malignancy cases in patients with thalassemia build new scenarios for the next few years. We describe the first report of a thalassemic patient developing diabetes and head and neck cancer and try to summarize the possible predisposing factors and mechanisms behind their phenomenon. Case presentation The current case report describes a 50-year-old Asian man who has been diagnosed with thalassemia since childhood. In early 2017, he was also diagnosed with diabetes and started on insulin-hypoglycemic treatment. The patient was then diagnosed with primary non-keratinizing undifferentiated carcinoma of the nasopharynx in late February 2013. A biopsy of the left tongue revealed squamous cell carcinoma (SCC) in late March 2019. Conclusions We report the first case of a thalassemic patient developing diabetes and squamous cell carcinoma of the head and neck and discuss the possibility of a link between the three diseases. This specific case should alert physicians to the possibility of endocrinopathy and malignancy in thalassemic patients.